Relationship of the ocular surface temperature with the clinical features of induced non-infectious anterior and intermediate uveitis in rabbits (Ukrainian Journal of Ophthalmology, 2025)
Background: It is an important challenge to develop objective methods for assessing intraocular inflammation.Purpose: To assess the relationship of the ocular surface temperature in the projection of the ciliary body with the clinical signs of induced non-infectious anterior and intermediate uveitis in rabbits.Material and Methods: Measurements of the ocular surface temperature in the projection of the ciliary body were performed in 17 Chinchilla rabbits with induced non-infectious anterior and intermediate uveitis.Results: The clinical signs of uveitis which characterize inflammatory activity were most pronounced on day 1 of induced non-infectious anterior and intermediate uveitis in rabbits, gradually decreased thereafter and were not observed by day 19. There was a weak correlation between the ocular surface temperature in the projection of the ciliary body and weighted score of the clinical signs of anterior and intermediate uveitis (r = 0.32; р = 0.0001) for all follow-up time points. The difference in temperature between the affected eye and the intact eye correlated with the weighted score of clinical signs of experimental uveitis activity. Thus, this correlation was strong (r = 0.73; р = 0.008) on day 1, became weaker on subsequent days, and became not significant from day 8 (r = 0.4; р = 0.19). The difference in the ocular surface temperature in the projection of the ciliary body between the affected eye and the fellow eye does not clearly represent an ocular temperature response to the induced disease due to the presence of the autonomic nervous system (ANS) response in the form of an increase in the temperature of the fellow eye. Therefore, the presence of this ANS response should be taken into account in calculations, and the comparison should be conducted against reference temperature values of intact eyes, but not against the fellow eye.
Keywords: uveitis; objectively assess inflammation; ocular surface temperature; thermoelectric device